ИЗУЧЕНИЕ ЗНАЧЕНИЯ БАЛХОТКОВ В МЕДИЦИНЕ С ПОМОЩЬЮ ФИЗИКО-ХИМИЧЕСКИХ МЕТОДОВ - Karimov J.S (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Marigolds contain many chemical substances. The presence of hydroxybenzoic acid derivatives and flavonoids in the plant is important in the prevention and treatment of inflammation and eye diseases.